Phytomyza trolliicaulis sp. n. (Diptera Agromyzidae) minatrice di Trollius europaeus L. (Ranuncolaceae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Viene descritta Phytomyza trolliicaulis sp. n., minatrice del caule di Trollius europaeus.
Keywords: Agromyzidae; Phytomyza trolliicaulis; Trollius europaeus